Global phosphoproteomic analysis reveals ARMC10 as an AMPK substrate that regulates mitochondrial dynamics - Zhen Chen (Nature Portfolio, 2019)
AMPK is regulates cellular energy and has been extensively studied, although our knowledge of downstream substrates is incomplete. Here, Chen et al. perform global quantitative analysis for AMPK-dependent sites and validate one hit, ARMC10, as a direct AMPK effector of mitochondrial dynamics.